Ancient Chinese political thought - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2021)
“Ancient Chinese political thought” refers to the reflections and discussions about politics during the period before the First Emperor established the Qin dynasty in 221 BCE. Although one could also infer some political thought of that period from the other archeological evidence, the main sources of such reflections and discussions are texts believed to date back to that period, some of which became the foundation of Chinese education that began in the Han dynasty (210 BCE–220 CE) and lasted till the beginning of the 20th century. Although disrupted by the turbulent history of China’s encounter with modernity in the early 20th century, the study of ancient Chinese texts has become the center of what is known as “national studies (guoxue 国学)” in the People’s Republic of China (PRC) today, with institutes devoted to it in many Chinese universities, supporting researchers from various disciplines. In the revival of Confucianism coupled with the rise of cultural nationalism in mainland China, many Chinese scholars have turned to ancient Chinese political thought for inspiration in their search for distinctively Chinese perspectives on politics, both local and global, and they advocate Chinese alternatives or models to address contemporary challenges. With limited space, the publications selected for this article make up only a small fraction of the works in English and even fewer in Mandarin that discuss ancient Chinese political thought. (The focus on English works is due to the consideration that not all readers of this article would be able to read Mandarin.) In addition to being studied as part of early Chinese civilization that has influenced Chinese society through subsequent centuries, political theorists and philosophers engage ancient Chinese political thought to address perennial or contemporary political problems, contributing significantly to the growth of comparative political theory and comparative political philosophy.